2021
DOI: 10.1177/21582440211046937
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Creativity and Work Engagement Through Perceived Organizational Support: The Interactive Role of Stressors

Abstract: The increasing interest of organizations in innovating and surviving during stressful work environments has led scholars to ponder ways to increase employee’s creativity. The study aims to empirically examine the relationship between perceived organizational support (POS) and employee creativity through work engagement and the moderating effect of challenge and hindrance stressors. The theoretical lens of social exchange theory was used to explain the study framework. Data was collected from 324 marketing pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 114 publications
3
16
0
1
Order By: Relevance
“…Research findings showed that, as predicted, employee engagement was found to positively influence IWB among the millennial employees working in the service industry. Such a finding is consistent with extant literature (Mansoor et al, 2020;Arifin et al, 2021;Inam et al, 2021;Svensson et al, 2021). Similarly, Al-Ajlouni (2021) and Gemeda and Lee (2020) reported similar findings and advocated the relevance of EE in encouraging employees' IWBs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Research findings showed that, as predicted, employee engagement was found to positively influence IWB among the millennial employees working in the service industry. Such a finding is consistent with extant literature (Mansoor et al, 2020;Arifin et al, 2021;Inam et al, 2021;Svensson et al, 2021). Similarly, Al-Ajlouni (2021) and Gemeda and Lee (2020) reported similar findings and advocated the relevance of EE in encouraging employees' IWBs.…”
Section: Discussionsupporting
confidence: 89%
“…Prior research indicated that EE has a significant positive influence on employees' IWB (Arifin et al, 2021). EE has a direct relationship with employee creativity among marketing personnel in the Pakistani context (Inam et al, 2021). Svensson et al (2021) underlined that EE is positively related to IWB.…”
Section: Employee Engagement and Innovative Work Behaviormentioning
confidence: 99%
“…Since the formation of creativity not only requires individuals to be motivated to try, but also requires individuals to have the confidence and ability to break through, previous studies have mostly analyzed the factors influencing creativity at a single "willingness" level, such as calling 68 and work engagement. 16,17 This study further enriches the exploration of creativity influencing mechanisms by exploring the formation of creativity at both the "willingness" and "ability" levels.…”
Section: Theoretical Contributionmentioning
confidence: 89%
“…15 In the digital era, science-technology talents with digital thinking can not only objectively view the organization's attitude toward them, as well as their status and value in the organization, and improve their emotional attachment to the organization, but they can also dialectically and critically view the vast amount of digital information, explore potentially useful information, improve resource utilization efficiency and innovation effectiveness, and enjoy innovative thinkers. The existing literature was primarily based on stressors, 16 work engagement, 17 and other perspectives to investigate the influencing factors of creativity without introducing elements of the digital era into the context of the digital era, and there were few studies on the creativity of science-technology talents, as well as the mechanism of the role of perceived organizational support and creativity in the digital environment.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike exhausted and disengaged disgruntled employees, engaged leaders & show increased enthusiasm for work, they take initiatives at work and relish their time at work (Bakker et al, 2008). Inam et al (2021) highlights that organization intentions toward engagement and support of employees can create positive attitude among employees. It aids in doing their job uniquely as they feel valued and being cared.…”
Section: Literature Review and Theoretical Underpinningsmentioning
confidence: 99%